2021
DOI: 10.3390/brainsci11091126
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Emotional Effects of Digital Technology on Children in COVID-19 Pandemic

Abstract: COVID-19 has caused obstacles in continuing normal life almost everywhere in the world by causing the implementation of social distancing and eventually imposing the lockdown. This has become the reason for the increase in technology usage in daily life for professional work as well as for entertainment purposes. There has been an increased prevalence of technology usage in adolescents and children during lockdown leaving its impact on their lives either in a positive or negative aspect. The overall documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 50 publications
1
68
0
4
Order By: Relevance
“…Some social predisposes are also likely to cause psychological discomfort and resulting mental illnesses in a university or college setup. Some early childhood preconditions are also likely to impact a person psychologically, even at the tertiary level of education ( 44 ). For instance, childhood trauma, abuse, and neglect are likely to be more disastrous when a person reaches the university or college level.…”
Section: Resultsmentioning
confidence: 99%
“…Some social predisposes are also likely to cause psychological discomfort and resulting mental illnesses in a university or college setup. Some early childhood preconditions are also likely to impact a person psychologically, even at the tertiary level of education ( 44 ). For instance, childhood trauma, abuse, and neglect are likely to be more disastrous when a person reaches the university or college level.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our results indicate that the intervention does not produce counterproductive effects. This is an important finding, because potential negative impacts of the usage of technology need to be taken into account [ 59 ] and simulating a house party may potentially induce positive outcome expectations with respect to alcohol use. Additionally, this finding corresponds to previous mixed methods research of the user experiences of VR FestLab , which identified that students experience VR FestLab very positively and praised it as a safe environment to explore careful and risk-taking game choices regarding alcohol intake [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scores show the reports on negotiation are still strong in the comments on the works proposed by the individuals and the search for a common agreement in the event of disagreement (points 12 and 20) on the final work to be proposed. The Melbourne scale of decision-making offers weaker outcomes [38]; the most significant data are concerned with the clarification of the objectives before choosing (item 18), acceptance of the group decision (21,27), pessimism about one's personal decision and delegation of responsibility to the group (22,26,29). Furthermore, the relationship between the three scales is very strong to highlight that DST has a strong effect on the three constructs investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused a profound change in the professional ways of teachers, training paths have been rethought through online teaching. In this context, the University of Foggia has experimented with a working model that facilitates firstperson experimentation (by teachers) on innovative teaching methodologies related to media education, gamification and the transfer of knowledge in the field of their daily professional practice [38]. The monitoring of these three dimensions represents a fundamental step for the future of online and hybrid teaching in schools, and the subsequent experimentation will concern the use of this model, both in collaborative teaching in the classroom (differentiated by age groups) and for inclusive teaching, oriented to specific learning needs.…”
Section: Methodsmentioning
confidence: 99%